Metagenomic insights into the distribution, mobility, and hosts of extracellular antibiotic resistance genes in activated sludge under starvation stress. (1st June 2023) - Zhou, Shuai; Yang, Zhengqing; Zhang, Siqi; Gao, Yuanyuan; Tang, Zhenping; Duan, Yi; Zhang, Yalei; Wang, Yayi
Highlights: eARG fate in starved sludge was explored by metagenomics for the first time. Aerobic C&N&P starvation achieved an optimal removal of eARGs and eMGEs. Singe N or P deficiency and anaerobic/anoxic starvation enriched some eMGEs. eARG hosts under starvation varied with substrate types and environmental conditions. Starvation decreased eARGs by altering eMGEs rather than the bacterial community. Abstract: Extracellular antibiotic resistance genes (eARGs) are important emerging environmental pollutants in wastewater treatment plants (WWTPs). Nutritional substrate deficiency (i.e., starvation) frequently occurs in WWTPs owing to annual maintenance, water quality fluctuation, and sludge storage; and it can greatly alter the antibiotic resistance and extracellular DNA content of bacteria. However, the fate and corresponding transmission risk of eARGs in activated sludge under starvation stress remain largely unknown. Herein, we used metagenomic sequencing to explore the effects of starvation scenarios (carbon, nitrogen, and/or phosphorus deficiency) and environmental conditions (alternating anaerobic-aerobic, anaerobic, anoxic, and aerobic) on the distribution, mobility, and hosts of eARGs in activated sludge. The results showed that 30 days of starvation reduced the absolute abundances of eARGs by 40.9%–88.2%, but high-risk dual and multidrug resistance genes persisted. Starvation, particularly the simultaneous lack of carbon, nitrogen, and phosphorus under aerobic conditions, effectively alleviated eARGs by reducing the abundance of extracellular mobile genetic elements (eMGEs). Starvation also altered the profile of bacterial hosts of eARGs and the bacterial community composition, the latter of which had an indirect positive effect on eARGs via changing eMGEs. Our findings shed light on the response patterns and mechanisms of eARGs in activated sludge under starvation conditions and highlight starvation as a potential strategy to mitigate the risk of previously neglected eARGs in WWTPs. Graphical abstract: Image, graphical abstract